Electrochemical Characterization of Recast Nafion® Film-Modified Electrodes in Acetonitrile with Various Electrolytes - Anna F. Claire; Peter Zacher; Danielle Lehto; Daysha Krahn; Krysti L. Knoche Gupta (Electrochem, 2024)
Nafion® is a cation exchange polymer that is commonly used in aqueous energy applications such as fuel cells due to its ability to exclude anions and neutral molecules and increase apparent diffusion of cationic redox molecules. However, this behavior is not well studied in nonaqueous solutions. The behavior of platinum electrodes modified with recast Nafion® films in nonaqueous solutions was observed to be different from its well-studied behavior in aqueous solutions. The reversible redox couple tris(2,2′-bipyridine)ruthenium(II) hexafluorophosphate was studied in the nonaqueous, aprotic solvent acetonitrile with different electrolytes (tetrabutylammonium tetrafluoroborate, tetrabutylammonium trifluoromethanesulfonate, tetrabutylammonium hexafluorophosphate, and ammonium trifluoromethanesulfonate) using cyclic voltammetry and rotating disk voltammetry. An unmodified platinum electrode in the nonaqueous systems and a recast Nafion®-modified platinum electrode equilibrated in an aqueous solution of tris(bipyridine)ruthenium(II)chloride hexahydrate were used as controls. Results indicate that the polymer structure in acetonitrile conditions does not allow apparent (Dahms–Ruff) diffusion but does allow significant physical diffusion that would make Nafion a great immobilization option for modifying electrodes with catalysts in nonaqueous systems.